Endocrinology Meets Metabolomics: Achievements, Pitfalls, and Challenges. (October 2017) - Tokarz, Janina; Haid, Mark; Cecil, Alexander; Prehn, Cornelia; Artati, Anna; Möller, Gabriele; Adamski, Jerzy
Abstract : The metabolome, although very dynamic, is sufficiently stable to provide specific quantitative traits related to health and disease. Metabolomics requires balanced use of state-of-the-art study design, chemical analytics, biostatistics, and bioinformatics to deliver meaningful answers to contemporary questions in human disease research. The technology is now frequently employed for biomarker discovery and for elucidating the mechanisms underlying endocrine-related diseases. Metabolomics has also enriched genome-wide association studies (GWAS) in this area by providing functional data. The contributions of rare genetic variants to metabolome variance and to the human phenotype have been underestimated until now. Trends: Metabolomics provides versatile functional phenotyping. The dynamics of the metabolome reflects gene–gene as well as gene–environment interactions. Distinct environmental challenges including nutrition, medication, and age reveal specific metabolomic signatures. Multiple endocrine disorders reveal unique metabolite signatures. Metabolomics-derived biomarkers have high potential for use in precision medicine.